HONEY VALUE CHAIN ANALYSIS: THE CASE OF ABUNA GINDEBERET DISTRICT OF OROMIA REGIONAL STATE, ETHIOPIA - BORENA, BESHA TERESA (Innovare Journal of Agricultural Sciences, 2023)
Annual honey production in Ethiopia was large by African standard. However, its limited value addition activities and poor collaboration between chain actors affect the entire chain. This study was conducted in Abuna Gindeberet district to map honey value chain, identify existing market channel and role of actors across the chain. Both primary and secondary (published and unpublished sources) data were collected. Totally 150 honey producer were selected using pre-tested structured questionnaire; and key informant interview for Traders and consumers; and focus group discussion used. Data were analyzed using descriptive and inferential statistics, aspects of value chain and STATA. Major honey actors include input suppliers, producers, collectors, wholesalers, processors, and consumers. Wholesalers are the main honey value chain governor and producer position in price negotiation and product quality definition is not good. Among producers 7.33% and 65.33% conduct upgrading using honey extractor and storing, respectively. Six market channels were identified and channel was the largest (volume) and channel IV is the longest. Thus, it was highly recommended to improve the inter-linkage to improve whole honey value chain actors and market channel from production to consumption.